The cremator - Fuks, Ladislav 1923-1994; Liška, Zdeněk 1922-1983 (<<The>> Criterion collection, 2020)
"Czechoslovak New Wave iconoclast Juraj Herz’s terrifying, darkly comic vision of the horrors of totalitarian ideologies stars a supremely chilling Rudolf Hrušínský as the pathologically morbid Karel Kopfrkingl, a crematorium manager in 1930s Prague who believes fervently that death offers the only true relief from human suffering. When he is recruited by the Nazis, Kopfrkingl’s increasingly deranged worldview drives him to formulate his own shocking final solution. Blending the blackest of gallows humor with disorienting expressionistic flourishes—queasy point-of-view shots, distorting lenses, jarring quick cuts-the controversial, long-banned masterpiece The Cremator is one of cinema’s most trenchant and disturbing portraits of the banality of evil." [criterion.com]
Original: Tschechoslowakei 1969
two-DVD special edition features: new 4k digital restoration ; high-definition transfer of 'The junk shop', director Juraj Herz's 1950 debut short film ; short documentary from 2011 featuring Herz visiting filming locations and recalling the production of 'The cremator' ; new interview with film programmer Irena Kovarova about the style of the film ; documentary from 2017 about composer Zdenek Liska featuring Herz, filmmakers Jan Svankmajer and the Quay Brothers, and others ; interview with actor Rudolf Hrusinsky from 1993 ; trailer ; new english subtitle translation ; plus an essay by film scholar Jonathan Owen
Bildformat 1.66:1
Keywords: Film; DVD-Video